Effects of chronic haloperidol and clozapine treatment on AMPA and kainate receptor binding in rat brain - Schmitt, Andrea; May, Brigitte; Müller, Bettina; Jatzko, Alexander; Petroianu, Georg; Braus, Dieter F.; Henn, Fritz A. (Pharmacopsychiatry, 2003)
Thieme E-Books & E-Journals